Anion‐Driven Reversible Switching of Metal‐Centered Stereoisomers in Metallopeptides. Issue 15 (11th March 2013) - Ousaka, Naoki; Takeyama, Yuki; Yashima, Eiji
<x xml:space="preserve">Abstract</x> Anion‐triggered chiral switch: Reversible switching between fac and mer isomers in tris(2, 2′‐bipyridine)iron(II) complexes, the ligands of which are substituted at the 5‐position with various peptides of different lengths and sequences, has been achieved (see figure). The remote stereocontrol at the FeII center by a domino‐type chiral information transfer along an achiral peptide main‐chain was observed even over 3 nm (50 bond lengths).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>